The Quality of Teaching-Learning Management of the Undergraduate Level at Souphanouvong University - inthavone, bouala; INTHAPANYA, Sangkhom; FAIPHENGYOUR, Yaly; SEUANGKINKEO, Amphanh; RATTANANONGSY, Sengmany; KITTIKHOUN, Sangviane (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The purpose of this study was to investigate the quality of teaching and learning management of the undergraduate level at Souphanouvong University. The sample group consisted of 420 individuals, including administrators, lecturers, and undergraduate students of the university. The research instruments were based on a 5-point Likert scale. The data were analyzed using frequency, mean, and standard deviation with computer software. The research findings revealed that the overall quality of teaching and learning management quality at the undergraduate at Souphanouvong University was at a good level, with an average score of (X̅ = 3.63, SD = 0.58). Among the various aspects, the characteristic of lecturers received the highest average score (X̅ = 3.75, SD = 0.71), followed by the curriculum (X̅ = 3.74, SD = 0.75), student characteristics (X̅ = 3.69, SD = 0.69), student support (X̅ = 3.65, SD = 0.80), teaching materials (X̅ = 3.64, SD = 0.75), teaching and learning processes (X̅ = 3.62, SD = 0.65), information systems (X̅ = 3.54, SD = 0.88), academic research services (X̅ = 3.51, SD = 0.83), and learning environment and resources, which received the lowest average rating (X̅ = 3.51, SD = 0.76).